Study of etiopathogenesis and various surgical techniques used in incisional hernia - Ray, Mausam; Mohapatra, Minati; Panda, Srikant; Sarangi, Ashok K.; Babu, K. Kiran; Sarangi, Anshuman (International Surgery Journal, 2022)
Background: Incisional hernia is the only abdominal hernia that is iatrogenic. For many years, the repair of incisional hernia was associated with a high recurrence rate. Laparoscopic technique of hernia repair has revolutionized the treatment of incisional hernia repair by reducing the morbidity and less hospital stay to the patient. With the above background we performed a study to analyse various etiological factors, study the age and sex incidence, time of occurrence of incisional hernia following various abdominal incision and to compare various surgical modalities based on size of incisional hernia. Methods: Patients admitted with incisional hernia during October 2017 to September 2019 at S. C. B. Medical College and hospital are taken up for study with the help of relevant history, clinical examination and appropriate investigations. Results: The mean age of the patients in open group is 45.66 years and 44.3 years in laparoscopy group. Out of the 51 patients in open group 13 (25.5%) are male while 38 (74.5%) are females where as in laparoscopy group, out of the 31 patients 10 (32.3) are males while 21 (67.7) are females. Out of 82 patients, maximum number of patients presented with swelling 60 (73.3%) followed by swelling and pain 19 (33.3%). The overall complication rate in open group was 45.09%, while in laparoscopy group it is 19.4%. Conclusions: The main etiological factors identified for the occurrence of incisional hernia were wound related complications, faulty techniques, comorbid conditions. Hence the incidence of the incisional hernia can be decreased by preventing these factors.